Kajian Manajemen Risiko pada Proyek Pembangunan di Kabupaten Aceh Jaya - Dedek Ariansyah; samin, muhammad; Heru Pramanda; Bunyamin Bunyamin; Muhajjir Muhajjir (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
Aceh Jaya Regency is one of the developing regions in Aceh, where infrastructure development is being intensified, particularly the construction of the Paya Baro - Teupin Ara road aimed at improving community accessibility due to previously damaged and inadequate road conditions. This study aims to identify and analyze the risks affecting project implementation and to formulate appropriate mitigation strategies. A quantitative approach was employed through the distribution of questionnaires to 35 respondents, consisting of the owner, consultants, contractors, workers, and local community, with data processed using Microsoft Excel and supported by validity and reliability testing of the research instruments. The results indicate that construction work factors are the dominant contributors to project risk, with the overall risk level predominantly classified as moderate (98), followed by low risk (31) and high risk (11), while no extreme risk was identified. These findings suggest that the project implementation is relatively under control; however, improvements in risk management are still required, particularly in planning, execution control, occupational safety, and environmental management. Therefore, this study provides valuable insights as a basis for decision-making to enhance the effectiveness of risk management in sustainable road construction projects.